2005
DOI: 10.4315/0362-028x-68.4.744
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Barotolerant Listeria monocytogenes in Sausage by Combination of High-Pressure Processing and Food-Grade Additives

Abstract: Food-grade additives were used to enhance the efficacy of high-pressure processing (HPP) against barotolerant Listeria monocytogenes. Three strains of L. monocytogenes (Scott A, OSY-8578, and OSY-328) were compared for their sensitivity to HPP, nisin, tert-butylhydroquinone (TBHQ), and their combination. Inactivation of these strains was evaluated in 0.2 M sodium phosphate buffer (pH 7.0) and commercially sterile sausage. A cell suspension of L. monocytogenes in buffer (10(9) CFU/ml) was treated with TBHQ at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Synergistic inactivation effects have been described when HHP treatments were combined with low pHs (15,25) or with different antimicrobial substances, such as lysozyme (16,18,30), pediocin (17,21,22), nisin (8,17,18,21,30,55), and lacticin (34). Several workers have reported the lethal effect of HHP in combination with phenolic antioxidants, such as TBHQ or butylated hydroxyanisole (8,27,58), or with plant essential oils, such as citral (41).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Synergistic inactivation effects have been described when HHP treatments were combined with low pHs (15,25) or with different antimicrobial substances, such as lysozyme (16,18,30), pediocin (17,21,22), nisin (8,17,18,21,30,55), and lacticin (34). Several workers have reported the lethal effect of HHP in combination with phenolic antioxidants, such as TBHQ or butylated hydroxyanisole (8,27,58), or with plant essential oils, such as citral (41).…”
Section: Discussionmentioning
confidence: 99%
“…TBHQ and HHP treatment also act synergistically when simultaneously applied to L. monocytogenes at pH 7.0 (8,58). We found that 100 ppm of TBHQ acting alone at pH 7.0 did not affect the survival of L. monocytogenes, in agreement with Vurma et al (58), but caused extensive sublethal injury following refrigerated storage for 24 h. This sensitizing effect might explain the efficacy of the combined treatment of HHP and TBHQ in L. monocytogenes, which allowed the inactivation of Ͼ6 log 10 cycles at pH 7.0.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations